Endoscopic ultrasonography is not required for staging malignant esophageal strictures that preclude the passage of a diagnostic gastroscope. Issue 6 (21st April 2016) - Bang, Ji Young; Ramesh, Jayapal; Hasan, Muhammad; Navaneethan, Udayakumar; Holt, Bronte A.; Hawes, Robert; Varadarajulu, Shyam
Abstract : Background and Aim: Endoscopic ultrasound (EUS) is considered the most sensitive modality for local staging of esophageal cancer (ECA) and current guidelines recommend EUS in all patients with non‐metastatic disease. Our aim was to identify a subset of patients with stenotic, non‐metastatic ECA who will not benefit from staging EUS. Methods: This multicenter study evaluated consecutive patients with newly diagnosed non‐metastatic ECA referred for local staging by EUS. All patients had endoscopic evaluation of malignant strictures with 9.8/9.9‐mm diagnostic gastroscope prior to EUS. Main outcome measure was to evaluate the relationship between degree of malignant stenosis and tumor staging by EUS. Results: Of 100 patients (median age, 65 years; male 81%), gastroscope could not be advanced past the stricture in 46, all of whom (100%) had locally advanced disease at EUS: T3N0/N+ in 39 and T4N0/N+ in seven. Echoendoscope could not traverse the stricture in any of these patients. Gastroscope could be advanced through the stricture in 54 patients in whom EUS staging was T1N0 in five, T2N0/N+ in eight and T3N0/N+ in 41; echoendoscope could not pass through the stricture in 24 of these 54 (44.4%) patients, all of whom had T3N0/N+ disease. On logistic regression analysis, inability to pass a gastroscope through the stricture was significantly associated with advanced (T3/4) tumor stage (OR = 28.7, 95% CI = 1.64–501.2; P = 0.021). Conclusion: Routine EUS examination may not be required in all patients with ECA as the inability to advance a diagnostic gastroscope past a malignant stricture correlates 100% with locally advanced disease on EUS.